Dancing with fireflies : a Chapel Springs romance - Hunter, Denise, 1968- (Hunter, Denise, 1968- Chapel Springs romance., 2014)
"Jade returns home to Chapel Springs after years of protecting her fragile heart. Then along comes Daniel, making her long to dance again.Creative and complicated, Jade McKinley felt like a weed in a rose garden growing up in Chapel Springs. When she left, she thought she'd never look back. But now, pregnant, alone, and broke, she has no other choice but to return.The mayor of Chapel Springs, Daniel Dawson, has been an honorary member of the McKinley family for years. While his own home life was almost non-existent, Daniel fit right into the boisterous McKinley family. He's loved Jade for years, but she always saw him as a big brother. Now that shes back, his feelings are stronger than ever. As Jade attempts to settle in, nothing feels right. God seems far away, she's hiding secrets from her family, and she's strangely attracted to the man whos always called her squirt." --